Research trends in high performance Parallel Input/Output for cluster environments - Ludwig, T. (Інститут програмних систем НАН України, 2004)
Parallel input/output in high performance computing is a field of increasing importance. In particular with compute clusters we see the concept of replicated resources being transferred to I/O issues. Consequently, we find research questions like e.g. how to map data structures to files, which resources to actually use, and how to deal with failures in the environment. The paper will introduce the problem of massive I/O from the user´s point of view and illustrate available programming interfaces. After a short description of some available parallel file systems we will concentrate on the research directions in that field. Besides other questions, efficiency is the main issue. It depends on an appropriate mapping of data structures onto file segments which in turn are spread over physical disks. Our own work concentrates on measuring the performance of individual mappings and to change them dynamically to increase performance and control the sharing of resources.